Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

Savoirs féministes : des outils transformateurs ? - Institut de recherches et d'études féministes
Pour cet épisode enregistré lors de la Foire féministe de l'IREF, nous nous penchons sur la question des savoirs et des pratiques féministes : comment reconnaître la richesse des différentes formes de savoirs ? Comment faire dialoguer les savoirs théoriques et les savoirs pratiques ? On explore comment la combinaison des différentes formes de savoirs peut finalement soutenir les luttes féministes et viser la transformation sociale. Avec: Rosemarie Fournier-Guillemette , Marie-Soleil Chrétien, Mylène Bigaouette, Jeanne et Ariane (Centre de solidarité Lesbien), Alexia de C'est pas notre genre, Reem al botmeh Épisode enregistré durant la Foire féministe de l'IREF (27, 28 février et 1er mars 2025 - https://sites.grenadine.uqam.ca/sites/dsj/fr/foire-feministe-feministes-dans-la-cite) . Monté et écrit par Juliette Chevet. Avec le soutien financier du CRSH.
Keywords: approches et analyses; asie; care; colonialisme; droits des femmes*; foire féministe; féminisme décolonial; groupes de femmes; histoire et politique; intersectionnalité; justice sociale; justice transformatrice; milieux de pratique; militance; palestine; point de vue situé; pédagogie; queer; recherches partenariale; régions géographiques; systèmes d'oppressions; thématiques; éducation